2004
DOI: 10.1152/ajpendo.00332.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high altitude and water deprivation on arginine vasopressin release in men

Abstract: Hamilton. Effects of high altitude and water deprivation on arginine vasopressin release in men. Am J Physiol Endocrinol Metab 286: E20-E24, 2004. First published September 3, 2003 10.1152/ ajpendo.00332.2003.-High-altitude exposure changes the distribution of body water and electrolytes. Arginine vasopressin (AVP) may influence these alterations. The purpose of this study was to examine the effect of a 24-h water deprivation trial (WDT) on AVP release after differing altitude exposures. Seven healthy males (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…Highaltitude exposure has been repeatedly shown to be associated with increased diuresis and natriuresis, and secondary haemoconcentration with decreased effective plasma volume [32,33]. These effects are essentially related to decreased ADH and aldosterone signalling at the collecting ducts [32,33]. Healthy volunteers rapidly brought to the altitude of 4,559 m typically presented with increased diuresis, CH 2 O/GFR and FE Na, in keeping with decreased renal tubular actions of both ADH and aldosterone [10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Highaltitude exposure has been repeatedly shown to be associated with increased diuresis and natriuresis, and secondary haemoconcentration with decreased effective plasma volume [32,33]. These effects are essentially related to decreased ADH and aldosterone signalling at the collecting ducts [32,33]. Healthy volunteers rapidly brought to the altitude of 4,559 m typically presented with increased diuresis, CH 2 O/GFR and FE Na, in keeping with decreased renal tubular actions of both ADH and aldosterone [10].…”
Section: Discussionmentioning
confidence: 98%
“…Highaltitude exposure has been repeatedly shown to be associated with increased diuresis and natriuresis, and secondary haemoconcentration with decreased effective plasma volume [32,33]. These effects are essentially related to decreased ADH and aldosterone signalling at the collecting ducts [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that chronic hypoxia causes marked activation of the sympathetic nervous system in healthy humans and increased SBP, despite normalisation of the arterial O 2 content with acclimatisation (24) . Increased secretion of catecholamine (24,25) , vasopressin (26) and adrenocorticotropin (27) may promote the development of hypertension by the renin-angiotensin-aldosterone system (28) . Corn gruel or hoecake is the staple food throughout the year in Hei Yi Zhuang.…”
Section: Discussionmentioning
confidence: 99%
“…6 A second relevant component of adaptation to altitude is an increase in urinary volume, associated with a reduced renal sensitivity to arginine vasopressin (AVP). 7 Recent studies revealed that the lack of increase in urinary volume and free water clearance has a relevant prognostic value for the onset of acute mountain sickness (AMS) in mountaineers reaching a high altitude (4880 m). 8 ET-1 is produced in the kidney, where it functionally antagonizes AVP.…”
mentioning
confidence: 99%